Mi primera Biblia - Moore, Eva.; Duendes Del Sur (Firm); American Bible Society (New York : Scholastic/Scholastic en Espanol, 2007)
Presents eight stories from the Old and New Testaments, including the story of Noah, the Nativity, and Jesus and the children. On board pages.
On board pages.
On cover "American Bible Society."
In Spanish.
Keywords: Bible stories, Spanish; Board books; Materiales en espanol